Relationship Between Gender, Immunization Status, and Vitamin A Supply with The Incidence of Pneumonia in Toddlers - Sakiguna, Muhamad; Irawan, Risky; Andriana, Ana; Supartha, Made (Jurnal Biologi Tropis, 2025)
Particularly in underdeveloped nations, acute lower respiratory tract infections, such as pneumonia, are a leading cause of sickness and mortality in children under five. Pneumonia risk factors include both external and intrinsic variables. The purpose of this study was to determine the relationship between gender, immunization status, and vitamin A administration with the incidence of pneumonia in toddlers at Praya Hospital, Central Lombok Regency in 2023. The analytical observational research method used a case control design. The sampling technique used purposive sampling. The data obtained were analyzed using the chi-square correlation test. The results of this study obtained respondents based on male gender as many as 56 respondents (56%), and female gender as many as 44 respondents (44%) with a p-value of 0.009. Respondents who had complete immunization status were 47 respondents (47%), and those who had incomplete immunization status were 53 respondents (53%) with a p-value of 0.000. Respondents who were given vitamin A were 82 respondents (82%) and those who were not given vitamin A were 18 respondents (18%) with a p-value of 0.001. There is a relationship between gender, immunization status, and vitamin A administration with the incidence of pneumonia in toddlers at Praya Hospital, Central Lombok Regency in 2023.